Identifying barriers associated with LGBT seniors’ housing: Opportunities moving forward in the Canadian context - Thomas, Ren; Blackmore, Holly; Gahagan, Jacqueline (Canadian Planning and Policy / Aménagement et politique au Canada, 2023)
This research aims to determine barriers to seniors’ housing options among the LGBT population in Canada. Using a qualitative analysis of open-ended questions from a survey of 970 LGBT seniors and housing providers across Canada, this paper discusses housing options for LGBT seniors and provides an overview of the implications for planning and operating LGBT-inclusive housing. Barriers identified by the LGBT community include: fear of discrimination, homophobia, transphobia and violence from staff and residents, housing affordability and availability, health challenges, feeling unsafe, intersectional barriers, and building maintenance. Barriers identified by housing service providers include: no current inclusion practices at their workplaces, lack of information for staff and seniors, health challenges for seniors and housing affordability. The findings discuss the potential for LGBT-specific seniors’ housing in Canada, and the role of housing service providers, health care providers, and planners in creating inclusive housing accommodations and services which meet the needs of all seniors. Approaches such as providing better information on housing choices to seniors, implementing anti-discrimination policies and LGBT competency training for housing providers and staff, providing affordable and accessible units, and LGBT community engagement in the development of housing are critical.